2019
DOI: 10.1016/j.jclepro.2018.09.202
|View full text |Cite
|
Sign up to set email alerts
|

Use of fly ash as eco-friendly filler in synthetic rubber for tire applications

Abstract: In this study, the relationship between an eco-friendly filler, fly ash, and the properties of Styrene-Butadiene Rubber (SBR)-based compounds was investigated. Rubber compounds were produced by internal mixer and curing characteristics were evaluated. The total content of filler was constant and the content of fly ash increased from 0 to 10 phr. In the evaluation of the rubber compounds, the main focus was the mechanical properties and adhesion of the SBR compounds. Adhesion between these compounds and steel w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 47 publications
1
46
0
Order By: Relevance
“…As for the wet grip, the addition of a higher amount of GTR also implies a higher amount of carbon black, forming agglomerates that reduce the flexibility needed at low temperatures. Ren et al [24] found similar behavior on SBR compounds filled with carbon black and fly ash. The results herein reported represent a novel and added value to the use of GTR as filler in SBR compounds, since it does not deteriorate the aforementioned requirements of fuel economy and driving safety relevant to the tire tread.…”
Section: Dynamic-mechanical Analysismentioning
confidence: 73%
See 1 more Smart Citation
“…As for the wet grip, the addition of a higher amount of GTR also implies a higher amount of carbon black, forming agglomerates that reduce the flexibility needed at low temperatures. Ren et al [24] found similar behavior on SBR compounds filled with carbon black and fly ash. The results herein reported represent a novel and added value to the use of GTR as filler in SBR compounds, since it does not deteriorate the aforementioned requirements of fuel economy and driving safety relevant to the tire tread.…”
Section: Dynamic-mechanical Analysismentioning
confidence: 73%
“…In the case of the filled compounds, a pre-mix of SBR, GTR, and TESPT was prepared in an internal mixer (Haake™ Rheomix 600, Thermo Fisher Scientific, Waltham MA, USA) at 100 • C and a rotor speed of 100 rpm during 7 min. The pre-mixed material was incorporated with the rest of ingredients in the two-roll mill for further mixing and improving the processability of the rubber compound, following the mixing protocol previously described [24].…”
Section: Materials and Compoundingmentioning
confidence: 99%
“…The fact that the fly ash is used is beneficial: production material costs are reduced, a lot of technical features of the produced materials are improved, and additionally, the amount of waste stored in landfills is reduced [28]. In this context, the fly ash from coal combustion seems like a valuable mineral resource for industry, although ashes from different suppliers have to meet certain requirements.…”
Section: Introductionmentioning
confidence: 99%
“…The main reason is that FA is formed by high‐temperature calcination and thus has high thermal stability, and the oxide additives such as SiO 2 , Al 2 O 3 and MgO can act as thermal stabilizers to improve heat resistance. More importantly, the interfacial bonding between mFA and PVC matrix is enhanced through the incorporation of ETi 4 , [ 28,42 ] and ball‐milling makes it possible for OH‐FA to bond more ETi 4 molecules.…”
Section: Resultsmentioning
confidence: 99%
“…[21][22][23][24][25][26] Since FA is composed of versatile active oxides, it can also be used as a filler for PVC composites. It can not only improve the mechanical and thermal characteristics of polymer composites, [27,28] but also reduce the cost. However, there is only a limited number of hydroxyl groups on the surface of FA, which may cause poor compatibility between FA and PVC, and thus prevent the transfer of mechanical stress applied to the composite and consequently facilitate the rupture of composites.…”
Section: Introductionmentioning
confidence: 99%